PENERAPAN MODEL PENDIDIKAN KARAKTER DI SD IT ALIEF MARDIYAH - wandika; Wahyuningsih, Asih; Nur Jannah, Widia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims ti determine the implementation of the character education model at SDIT Alief Mardiyah and identify the factors that support and hinder its implementation. Character education is an important aspect in shaping the personality of students who are noble and responsible, especially in the midst of the challenges of the times and technological advances. This research uses a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, interviews and documentation with principals, teachers and students. The results showed that character education at SDIT Alief Mardiyah is implemented systematically through various religius habituation programmes such as dhuha prayer in congregation, tahfidz AL Qur’an, 5S habituation (slime, greeting, greeting, politenees, courtesy), and anti bullying programs. Teachers and principals play an active role as role models and drivers in character building activities. The supporting factors in the implementationof character education include a conducive school environment, support from teachers, and ctructured school programs, while the inhibiting factors include the lack of comprehensive parental involvement and the challenge of negative influences from social media. In conclusion, the implementation of the character education model at SDIT Alief Mardiyah runs quite effectively and is able to form student’s religious, disciplined and responsible personalities. However, stronger cooperation between the school and parents is needs to support the sustainability of this program.